Fever and Hip Pain: Not Always Due to a Septic Hip. Issue 12 (December 2018) - Waseem, Muhammad; Kumari, Divya; Toledano, Talya
Abstract : Abstract: Hip pain in febrile children always raises concern for septic arthritis. Pyomyositis is a rare cause of hip pain. Because it involves muscles around the joint, it may have a similar presentation as a septic hip. This entity therefore has the potential for posing a diagnostic dilemma when physicians face a limping child with fever. We report a child who presented with fever and hip pain and has pyomyositis of the obturator internus muscle. This case underscores the need to consider the possibility of alternative etiologies in a limping child.